Respon Populasi Kutu Daun Persik Terhadap Pemberian Beberapa Jenis Ekstrak Kulit Jeruk pada Cabai - Nur Raisa Amalina; Subagiya Subagiya; Ato Sulistyo (Universitas Sebelas Maret, 2018)
Myzus persicae is the main pest in chili which causes decreasing production and qualities of chili. The was aimed to know the effect of Pomelo and Orange’s peel extract to controlling green peach aphids population. The research was conducted in screen house located in Colomadu, Karanganyar regency from October 2017- January 2018. This research used Randomized Complete Design with 2 factors i.e variety of orange’s peel extract and levels of concentration. The various Citrus’s peel extract consisted of Pomelo’s peel extract and Orange’s peel extract. Levels of concentration from each extracts i.e 1%, 2%, 4%, 8%, and 16%. Each treatment replicated 5 times. The result showed that Citrus peel extracts had effect on the green peach aphid population and had no effect on the growth of chili. The LC50 value of Pomelo and Orange’s peel extracts were 4,77% and 5,56%. Pomelo and orange peel extract treatment on differrent concentration was not give effect on the percentage of the attack intensity.